2023
DOI: 10.1186/s13031-023-00531-y
|View full text |Cite
|
Sign up to set email alerts
|

A syndemic of inequitable gender norms and intersecting stigmas on condom self-efficacy and practices among displaced youth living in urban slums in Uganda: a community-based cross-sectional study

Moses Okumu,
Carmen H. Logie,
Anissa S. Chitwanga
et al.

Abstract: Background Adverse socio-cultural factors compromise the implementation of HIV prevention strategies among displaced youth. While condoms are an affordable and effective HIV prevention strategy for youth, stigma and inequitable gender norms may constrain condom self-efficacy (i.e., knowledge, intentions, and relationship dynamics that facilitate condom negotiation) and use. Further, knowledge of contextually appropriate HIV prevention approaches are constrained by limited understanding of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…A study in Honduras found that early childbearing in a girl's social network increased her likelihood of adolescent childbearing ( Shakya et al, 2020 ). Inequitable gender norms among adolescents may also condone males' entitlement to sex, or impede females' ability to insist on condom use ( Okumu et al, 2023 ; Pulerwitz & Barker, 2008 ; Shai et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Honduras found that early childbearing in a girl's social network increased her likelihood of adolescent childbearing ( Shakya et al, 2020 ). Inequitable gender norms among adolescents may also condone males' entitlement to sex, or impede females' ability to insist on condom use ( Okumu et al, 2023 ; Pulerwitz & Barker, 2008 ; Shai et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%